BREAKING GENDER STEREOTYPES: A CRITICAL APPRAISAL OF BARRIERS TO EFFECTIVE COMMUNICATION - Joy Amarachi Ofordi; Babatunde Joseph Ayodele (International Studies Journal)
The distributional structure of the world's languages is heavily influenced by gender stereotypes (lewis and Lupyan, 2020) and have been demonstrated to be stable over time, with relatively few changes to the fundamental gender roles (Haines 2016). This contributes to difficulty in communicating effectively. This paper, specifically identify the ways gender stereotypes can create barriers to effective communication, the negative implications of these barriers as well as propose strategies for breaking down these stereotypes and improving communication outcomes. Drawing strength from Gender and Communication theory, the paper explores how societal norms, media representations, power dynamics, and institutional practices influence communication patterns and hinder the breaking of gender stereotypes. Women are sometimes referred to, as the weaker sex because they are more easily subjugated by strong, physically dominant men who are also able to support their family. It discovered that stereotypes of these nature can lead to a number of barriersincluding disrespect, invisibility, discrimination and microaggressions as people may make subtle, yet harmful comments or behaviours that reinforce gender stereotypes, and hindering effective communication. The paper, therefore, recommends that it is important to be aware of the ways that gender stereotypes can impact communication by first, examining our own biases and assumptions as individuals, and organisations, about gender roles in communication. It is also important to challenge these stereotypes in order to create a more inclusive and equitable communication environment.